Array - Herawati, Pudji; Julaikah, Dwi Imroatu (LATERNE, 2021)
The listening process needs the complex activities such as high vision and appreciation required to understand the material and achieve learning goals. Based on research data from Moscow University of Russian, listening skills is difficult skills so there is a need for teaching materials that can be easily learned by students. Www.linguaTV.com is a web that offers 11 language functions that consist of audio and video teaching materials, games and exercises, depending on the language level. The video New in Berlin Coffee and Cake from the Internet www.linguaTV.com is an alternative teaching material that can be used. The problem with this investigation is how the suitability of the material in the video "New in Berlin - Coffee and Cake" as additional teaching material for listening skills for class XI, semester 2.d. The aim of this investigation is the result of the analysis of the suitability of the video material "New in Berlin-Kaffe und Kuchen" as additional teaching material for listening skills. This article uses a type of literature study with a qualitative approach. analyzed based on video sources and according to essen und trinken with niveau A1. This article was analyzed using material selection criteria based on Pr?tzner and Prastowo's theory from the literature study. The results of the analysis show that the material in the video Neu di Berlin-Kaffe und Kuchen is in accordance with the criteria for teaching materials and the curriculum, namely 1) the video is relevant to the substance of the material 2) the suitability of the material with the competence and curriculum 3) not too long in duration 4) interesting content and 5 and originality. Through the analysis process, it was found that the video Neu in Berlin-Kaffee und Kuchen has material compatibility with the curriculum and can be used as additional teaching material in learning German. Keywords: Video, Additional Teaching Materials, Listening Learning